Tracing trends in the sequences of dry and wet days over Peninsular Malaysia - Mohd. Deni, Sayang (Asian Network for Scientific Information, 2008)

(untitled)
This study attempts to trace changes in the dry and wet spells over Peninsular Malaysia based on the daily rainfall data from twenty rainfall stations which include four sub-regions, namely; northwest, west, south and east for the period of 1975 to 2004. Nine indices for each dry and wet spells comprising of the main characteristics for each spell, the persistency and the frequency of the various length of dry (wet) spells will be used to identify whether or not these indices have increased over Peninsular Malaysia. The Mann-Kendall (MK) trend test indicate that as the persistency of wet days is increased, the trend of the frequency of long wet spells is also found to be increased in most stations over the peninsula; however, decreasing trend is observed in the frequency of short spells in these stations. The frequency of long dry periods tends to be higher with a significant increase in the mean and variability of the length of the dry spells over the southern areas; whereas, all the indices of wet spells in these areas show a decreasing trend. Furthermore, over the western areas, all the indices of dry spells exhibit a negative trend and at the same time, the frequency of short wet spells exhibits a negative trend with an increase in the mean, variability and the persistency of the wet spells. Generally, no significant trend is found in most of the indices of dry (wet) spells in most stations over the northwestern and eastern areas for the period of 1975 to 2004